Perceived barriers and facilitators to HPV vaccination: Insights from focus groups with unvaccinated mid-adults in a U.S. medically underserved area - Sandya Krishna; Andrea N. Polonijo (Taylor & Francis Group, 2024)
Shared clinical decision-making (SCDM) about HPV vaccination has been recommended for U.S. mid-adults aged 27-45 since 2019. To explore barriers and facilitators to HPV vaccination in this population, we conducted 14 virtual focus groups with 86 unvaccinated mid-adults (34 men and 52 women) in California's medically underserved Inland Empire between September 2020 and January 2021. We systematically analyzed the focus group data using the rigorous and accelerated data reduction (RADaR) technique to identify key themes. Identified barriers included: lack of awareness, vaccine hesitancy, and perceived unaffordability (cited in 14 groups); lack of healthcare provider communication and insufficient time (13 groups); fear of moral judgment (12 groups); lack of motivation and information needs (10 groups); and lack of reliable transportation and foregone care during the COVID-19 pandemic (3 groups). Proposed facilitators included: tailored HPV vaccine information for mid-adults, cost mitigation, and improved vaccine accessibility (12 groups); healthcare provider-initiated conversations (6 groups); and vaccine reminders (4 groups). These findings highlight challenges to HPV vaccination among U.S. mid-adults eligible for SCDM and point to actionable strategies for improvement. Specifically, tailored educational interventions, decision-making tools for pharmacists, and integrating HPV vaccination into other healthcare encounters may enhance vaccination efforts in areas with limited primary care resources.